Readers' Reception of Satin Merah Detective Novel as a Literary Learning Material in Senior High School - Sasongko, Tegar Sulistya; Supriyanto, Teguh; Doyin, Mukh (Universitas Negeri Semarang, 2020)
Literary learning materials are one of the important components used by teachers in learning activities. Good learning materials can help students achieve learning goals. Sources of literature learning materials tend to focus on reference books from the government. Even though there are still many literary learning materials that can be used, one is novel. The research objective was to describe the teacher's response to Satin Merah's novel by Brahmanto Anindito and Rie Yanti as literary learning material at Senior High School. This research uses a pragmatic approach. The research is based on the reception of Indonesian language teachers at the Senior High School level on the feasibility of a novel based on the feasibility assessment of the BSNP in terms of content, language, and presentation. This study indicates that Satin Merah's novel's feasibility level is 82.5%, which means that this novel is feasible and has a good reputation as literary learning material at Senior High School. The feasibility results are shown in terms of content feasibility of 84.2%, language feasibility of 81.5%, and presentation feasibility of 82%. In terms of content, this novel develops self-potential, has creativity and depth of story, and develops readers' characters to love and preserve local culture. In terms of language, the language used is following Indonesian rules and according to the target audience. In terms of presentation, this novel pays attention to the building blocks and mostly develops characters and inspires readers.